The Economic Impact of Cystic Echinococcosis in Rio Negro Province, Argentina - Bingham, Glenda M. (Am J Trop Med Hyg, 2016)
Cystic echinococcosis (CE), a parasitic zoonosis with substantial human health and economic consequences, is highly endemic in Rio Negro Province, Argentina. The objective of this study was to estimate the direct and indirect human and livestock-associated monetary losses attributable to CE, in Rio Negro Province, for the year 2010. Human costs were estimated using data obtained from hospital chart reviews, patient interviews, and government reports. Livestock-associated losses were estimated using data from government reports and scientific publications. Spreadsheet models were developed utilizing Latin Hypercube sampling to account for uncertainty in the input parameters. In 2010, the estimated total cost of CE, in Rio Negro Province, ranged from US$4,234,000 (95% credible interval [CI]: US$2,709,000–US$6,226,000) to US$5,897,000 (95% CI: US$3,452,000–US$9,105,000), with livestock-associated losses representing between 80% and 94% of the total losses, depending on whether non-healthcare-seeking human cases were included and if livestock slaughter values were adjusted to account for underreporting. These estimates suggest that CE is responsible for considerable human and livestock-associated monetary losses in Rio Negro Province. Stakeholders and policymakers can use these data to better allocate public health and agricultural resources for this region.